The fast rise of the unusual type IIL/IIb SN 2018ivc - Reguitti, A. (2024)
We present an analysis of the photometric and spectroscopic dataset of the type II supernova (SN) 2018ivc in the nearby (10 Mpc) galaxy Messier 77. Thanks to our high-cadence data, we observed the SN rising very rapidly by nearly three magnitudes in five hours (or 18 mag d‑1). The r-band light curve presents four distinct phases: the maximum light, which was reached in just one day, followed by a first, rapid linear decline and a short-duration plateau. Finally, the long, slower linear decline lasted for one year. Thanks to the ensuing radio re-brightening, we were able to detect SN 2018ivc four years after the explosion. The early spectra show a blue, nearly featureless continuum, but the spectra go on to evolve rapidly; after about ten days, a prominent Hα line starts to emerge, characterised by a peculiar profile. However, the spectra are heavily contaminated by emission lines from the host galaxy. The He I lines, namely λλ5876,7065, are also strong. In addition, strong absorption from the Na I doublet is evident and indicative of a non-negligible internal reddening. From its equivalent width, we derived a lower limit on the host reddening of AV ≃ 1.5 mag. From the Balmer decrement and a match of the B ‑ V colour curve of SN 2018ivc to that of the comparison objects, we obtained a host reddening of AV ≃ 3.0 mag. The spectra are similar to those of SNe II, but with strong He lines. Given the peculiar light curve and spectral features, we suggest SN 2018ivc could be a transitional object between the type IIL and type IIb SNe classes. In addition, we found signs of an interaction with the circum-stellar medium (CSM) in the light curve, also making SN 2018ivc an interacting event. Finally, we modelled the early multi-band light curves and photospheric velocity of SN 2018ivc to estimate the physical parameters of the explosion and CSM.